(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article provides a comparative, legal and scientific analysis of the specifics of criminal liability for the illicit trafficking of weapons under French criminal law and the norms of liability for such crimes in the Criminal Code of the Republic of Uzbekistan, and offers suggestions for improving national legislation.